2018
DOI: 10.3390/agriculture8050064
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Date Palm Tree Density to Dubas Bug Ommatissus lybicus Infestation in Omani Orchards

Abstract: Date palm trees, Phoenix dactylifera, are the primary crop in Oman. Most date palm cultivation is under the traditional agricultural system. The plants are usually under dense planting, which makes them prone to pest infestation. The main pest attacking date palm crops in Oman is the Dubas bug Ommatissus lybicus. This study integrated modern technology, remote sensing and geographic information systems to determine the number of date palm trees in traditional agriculture locations to find the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The low relationship with temperature is attributed to tree density, which reduces the interchange of microclimate inside the date palm plantation and at the same time increases the effect of humidity. Earlier studies showed a positive relationship between tree density and O. lybicus infestation . The highly infested location (V4) for both seasons was associated with lower humidity, which enabled the effect of temperature to be clear.…”
Section: Discussionmentioning
confidence: 88%
“…The low relationship with temperature is attributed to tree density, which reduces the interchange of microclimate inside the date palm plantation and at the same time increases the effect of humidity. Earlier studies showed a positive relationship between tree density and O. lybicus infestation . The highly infested location (V4) for both seasons was associated with lower humidity, which enabled the effect of temperature to be clear.…”
Section: Discussionmentioning
confidence: 88%
“…The MODIS VCF data used in our study, for example, have the limitation that it only provide estimates of vegetation cover and does not provide information on whether trees are part of a natural forest or of a monospecific plantation. This might be problematic, for example increasing density of monocultures can show insect abundance trends which differ from patterns typically observed in natural forests, such as increased pest infestations (e.g., Al Shidi, Kumar, Al‐Khatri, Albahri, & Alaufi, ). Neither does it provide information on other forest characteristics, such as tree age and level of disturbance, which also influences insect community structure (Perry et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The irregular planting pattern of date trees results in high tree density per unit area, and higher density was reported to have a positive relationship with O. lybicus infestation [26]. Latifian et al [41] reported that the intensity of other pest species on date palm plantation was significantly higher when there are shorter distances between date palm trees.…”
Section: Discussionmentioning
confidence: 99%
“…The high-density trees and intercropping provide a good microclimate for insect increases and good fertilizer application provides more nutrients to the plants which is a preference of insects. Moreover, other studies have explored the relationship of O. lybicus infestation with different abiotic factors, solar radiation [25], tree density [26] and temperature and humidity [27]. High solar radiation with high temperature increases the body thermal accumulation, increasing metabolic activity which disrupts insect physiology [28]; however, high tree density reduces the interaction of outside weather, which increases the insect population [26].…”
Section: Introductionmentioning
confidence: 99%